2014
DOI: 10.2217/nnm.13.93
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency-Triggered Release for On-Demand Delivery of Therapeutics From Titania Nanotube Drug-Eluting Implants

Abstract: The results of this study show that RF is a promising strategy for triggered release from implantable drug delivery systems where on-demand delivery of therapeutics is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…The post‐formed PFH MBs significantly enhanced the contrast of US imaging (Figure c 2 and c 3 ). In addition, radiofrequency (RF) ablation has been widely used for minimally invasive and localized tumor hyperthermia, which is also considered as the irradiation source to trigger the phase transformation of droplets and generate MBs. For instance, solid DL‐menthol (DLM, melting point: 32–36 °C) was encapsulated into PLGA nanocapsules .…”
Section: Nanoparticulate Cas For Responsive Us Imagingmentioning
confidence: 99%
“…The post‐formed PFH MBs significantly enhanced the contrast of US imaging (Figure c 2 and c 3 ). In addition, radiofrequency (RF) ablation has been widely used for minimally invasive and localized tumor hyperthermia, which is also considered as the irradiation source to trigger the phase transformation of droplets and generate MBs. For instance, solid DL‐menthol (DLM, melting point: 32–36 °C) was encapsulated into PLGA nanocapsules .…”
Section: Nanoparticulate Cas For Responsive Us Imagingmentioning
confidence: 99%
“…As the most promising photocatalyst, titania materials (TiO 2 ) have been expected to play an important role in a wide range of fields including environmental pollution control, photocatalyst, and high effect solar cell due to their excellent physicochemical properties such as relatively high photocatalytic activity, thermal and chemical stability, nonphoto corrosive, being nontoxic, being capable of photooxidative destruction of most organic pollutants, and low cost [1][2][3][4][5]. Numerous recent research has shown that the photocatalytic activity of titania materials is mainly influenced by the surface area, grain size, crystallinity, crystal structure, band gap, and so forth [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro drug release with the aid of polymeric micelles as drug nano-carriers [93][94] and targeted drug release by means of Smart Drug Delivery Systemgold nanoparticles stimulated by radiofrequency field [95] and magnetic nanoparticles under the influence of a magnetic nanoparticles that are under the influence of a magnetic field [96].…”
Section: Nanoporous Engineered Drug Deliverymentioning
confidence: 99%